Changes in subfoveal choroidal thickness and reduction of serum levels of vascular endothelial growth factor in patients with POEMS syndrome. Issue 6 (4th October 2016) - Yokouchi, Hirotaka; Baba, Takayuki; Misawa, Sonoko; Kitahashi, Masayasu; Oshitari, Toshiyuki; Kuwabara, Satoshi; Yamamoto, Shuichi
Abstract : Aims: To determine the changes in the subfoveal choroidal thickness (CT), the foveal thickness (FT) and the serum level of vascular endothelial growth factor (VEGF) after thalidomide treatment in patients with polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin changes (POEMS) syndrome. Methods: We studied 13 left eyes of 13 treatment-naïve patients with POEMS syndrome. The subfoveal CT and FT were determined by enhanced depth imaging optical coherence tomography, and the serum level of VEGF was determined by ELISA at the baseline and at 6 months after thalidomide treatment. The correlations in the serum level of VEGF and the subfoveal CT or the FT at the baseline and at 6 months after treatment were determined. Results: Together with the reduction in the serum level of VEGF, the subfoveal CT was also reduced significantly from 439.1±66.5 µm at the baseline to 307.2±75.4 µm at 6 months (p=0.001). The mean FT at the baseline was 236.4±30.7 µm which did not change significantly at 6 months at 228.1±33.1 µm (p>0.05). The change in the subfoveal CT was significantly and linearly correlated with the change in the serum level of VEGF at 6 months after treatment (r=0.67, p=0.011). Conclusions: The significant correlation between the CT and the serum level of VEGF may offer clues on the pathogenesis of ocular diseases of POEMS syndrome and on the role of serum VEGF on the choroid.